The theory of "priority arrangements" between Western theorizing and application within the Arab environment - Faiea BAKKAR; Bent taa Allah BAKKAR (Social Sciences Journal, 1970)
A theory is a set of concepts, definitions, and assumptions that give us an organized view of a phenomenon, by defining the different relationships between the variables of that phenomenon, with the aim of explaining that phenomenon and predicting it in the future. It is a point of view, but based on a scientific basis, that explains what is happening or explains the relationship between things. It can go beyond that to predict what would happen if certain elements came together.